KESENJANGAN DISTRIBUSI TENAGA KESEHATAN DI PUSKESMAS WILAYAH INDONESIA TIMUR (Analisis Data IFLS East 2012) - Nurul Hikmah B.; Lutfan Lazuardi; Dwi Handono (Journal of Health Service Management, 2016)
Background: Since 1980s the Ministry of Health has usedseveral approaches to determine staffing needs, usingprojections based on public health status, demographicchanges and health programs that exist. This study describesthe distribution of health personnel gap in eastern Indonesiadue to see the injustice of health workers in eastern Indonesiaso that the government can deal seriously and firmly to theproblems of the distribution of health personnel, particularlyareas that are difficult to reach. Purpose: This study aims to determine the unequal distributionof health personnel in the health centers in Eastern Indonesia. Methods: This study is a quantitative research with quantitativemethods using cross sectional design. Using a large-scalesecondary data from the Indonesia Family Life Survey (IFLS)East. Results: This study indicate that there is a big gap in equity ofhealth workforce in primary health care in eastern Indonesiaexperienced vacancies even some of primary health care bothdoctors, nurses, midwives and midwife. This is evident from thedistribution of health personnel imbalance between primarycare located in areas with high and low number of population;high and low poverty rates; geographic location based on theurban/rural and remoteness even provinces. Conclusion: Primary health care in eastern Indonesia moreexperienced vacancies in particular labor of doctors andmidwives, as well as the low number of community healthworkers to prove that primary health care is oriented onpromotive and preventive neglected. Optimizing the role ofgovernment as a regulator and facilitator to give more focus andhelp the areas that lack health worker especially in the provinceof East Nusa Tenggara, Maluku and West Papua are more likelyto be a shortage of public health vacancy even doctors andmidwives.